Simultaneous Estimation of Quinapril Hydrochloride and Hydrochlorothiazide from Pharmaceutical Formulation by Using UV, IR and RP-HPLC - Tukaram Gawande, Vandana; Birajlal Miniyar, Pankaj; Dattatray Bhandari, Deepali; Kailas Ghag, Manasi; Bhikamsingh Rajput, Dhananjaysingh; Mahajan, Avinash (Asian Journal of Chemistry, 2014)
The objective of present investigation was to develop and validate assay methods for simultaneous estimation of quinapril hydrochloride and hydrochlorothiazide in combined dosage form by using three different analytical approaches viz. UV, FT-IR and RP-HPLC. Drugs were estimated by dual wavelength method and calibration curve methods by using UV and FT-IR spectrophotometer, respectively. The stability indicating assay method was developed by using HPLC. The stress degradation study was carried out according to International Conference on Harmonization (ICH) guideline Q1A (R2). Chromatographic separation was carried out on HIQ-Sil (150 × 4.6 mm, 5 μm) column using 0.01 M KH2PO4 buffer (pH 3.5, adjusted with orthophosphoric acid): methanol as mobile phase in gradient elution mode.